Evaluation of LiangXue JieDu Therapy in Combination With Western Medicine for Acute-On-Chronic Liver Failure: A Systematic Review and meta-Analysis - Shi, Ke; Zhang, Qun; Hou, Jie; Zhang, Yi; Bi, Yufei; Wang, Xianbo (Frontiers in Pharmacology, 2022)
Objectives: To assess the efficacy of LiangXue JieDu (LXJD) therapy in combination with Western medicine (WM) for acute-on-chronic liver failure (ACLF). Methods: Articles on randomized controlled trials of LXJD therapy for ACLF were obtained from PubMed, Embase, Cochrane Library, Web of Science, Chinese National Knowledge Infrastructure, VIP, Wanfang, and China Biology Medicine databases, with the search range from database inception to March 2022. We evaluated the quality of data from these articles using the Cochrane risk-of-bias tool. Evaluation indicators were total effective rate, mortality rate, complications, liver and coagulation function, and Traditional Chinese medicine (TCM) syndrome score. We then calculated the risk ratio (RR) for dichotomous variables and mean difference (MD) for continuous variables with a 95% confidence interval (CI). Results: The meta-analysis included 18 studies with moderate quality and totaling 1609 patients. Compared with WM alone, LXJD therapy plus WM improved total effective rate (RR = 1.34, 95% CI: [1.24, 1.45]), while reducing mortality rate (RR = 0.54, 95% CI: [0.42, 0.70]) and complications (RR = 0.43, 95% CI: [0.26, 0.71]). The combined treatment also improved prothrombin activity (MD = 1.30, 95% CI: [1.02, 1.59]), prothrombin time (MD = -0.90, 95% CI: [-1.40, -0.39]), international normalized ratio (MD = -0.59, 95% CI: [-0.93, -0.25]), alanine aminotransferase (MD = -0.92, 95% CI: [-1.30, -0.55]), aspartate aminotransferase (MD = - 0.57, 95% CI: [-0.93, -0.21]), total bilirubin (MD = -1.07 , 95% CI: [-1.38, -0.76]), and TCM syndrome score (MD =-1.70; 95% CI: [-2.03, -1.37]). Conclusions: This study suggests that LXJD therapy plus WM can significantly improves ACLF clinical symptoms and short-term outcomes. However, more high-quality trials are required to confirm the efficacy of LXJD therapy.